Sodium-electropolyanion positive electrode material as well as preparation method and application thereof

Through the combined use of graphene, β-cyclic paste and nano-zinc oxide, the problem of poor conductivity of iron-based hybrid hybrid phosphate NA4FE3 (PO4) 2P2O7, realizing the high electrical and excellent of sodium electrococcular pineral positive materials and excellent Electrochemical performance.

CN119381425APending Publication Date: 2025-01-28ZHUHAI NAYI NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411355381.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The electron conductivity, discharge capacity and rate performance of iron-based mixed phosphate Na4Fe3(PO4)2P2O7 has poor electronic conductivity, poor discharge capacity and rate performance, resulting in limited application in sodium ion batteries.

Method used

Through the combined use of graphene, β-cyclic paste and nano-zinc oxide, a uniform dispersed mixture is formed and is evenly covered with the surface of the positive electrode material, providing electronic transfer channels to improve the electrical and electrochemical properties of the material.

Benefits of technology

It significantly improves the conductivity and electrochemical properties of sodium electro -polycopic ion positive materials, improves the discharge capacity and circulation performance of the material, and has excellent percentage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a sodium electropolyanion positive electrode material as well as a preparation method and application thereof. Beta-cyclodextrin, graphene oxide and ZnO nanoparticles are self-assembled to serve as a coating layer material through supramolecular host-guest interaction, the coating layer material is mixed with a sodium source, a phosphorus source, an iron source and a carbon source, sanding, spraying and sintering are performed, and the sodium-electropolyanion positive electrode material is obtained. The obtained sodium-electric polyanion positive electrode material has high conductivity and electrochemical performance, the lithium iron phosphate composite material is prepared through a composite coating route of zinc element co-doping and carbon coating layer synergistic effect, the capacity exertion and rate performance of the sodium-electric polyanion material are guaranteed, and meanwhile the excellent cycle performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode material preparation, and specifically relates to a sodium polyanion positive electrode material and a preparation method and application thereof. Background Art

[0002] Iron-based mixed phosphate Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 It is a sodium ion battery cathode material with a polyanion structure, and its theoretical reversible specific capacity is 129 mAh g -1 , has excellent electrochemical sodium storage performance, low raw material cost, safety and environmental protection, and is a sodium ion battery positive electrode material with great development potential. 4 3- The electronic insulation of the group leads to low electronic conductivity and slow ion diffusion of the iron-based mixed phosphate, resulting in poor conductivity, lower actual specific capacity than theoretical specific capacity, lower coulombic efficiency, unsatisfactory discharge capacity at high rate, etc. In order to overcome these defects, technicians in this field have conducted a variety of exploratory experiments.

[0003] Chinese patent application publication number CN109301195A discloses a high-conductivity lithium iron phosphate material and its preparation method, wherein lithium iron phosphate is sintered at high temperature with graphene slurry, vapor-grown carbon fiber VGCF or carbon nanotubes, and a precursor containing precious metals to obtain a high-conductivity lithium iron phosphate material. The high conductivity of graphene, the bridging effect of carbon fiber, and the extremely high conductivity of precious metals are comprehensively utilized, thereby greatly improving the high-rate discharge performance of the lithium iron phosphate battery system. However, the dispersibility of graphene in this invention is general, and it is easy to deposit during the coating process, which affects the effect of graphene and lithium iron phosphate.

[0004] Chinese patent application publication number CN 117810403 A discloses a positive electrode material and its preparation method and application, which discloses: (1) dissolving zinc salt and γ-cyclodextrin in a solvent to obtain a mixed solution; (2) adding 2-methylimidazole to the mixed solution for reaction, and then drying after aging to obtain a cyclodextrin-modified metal organic framework; (3) mixing the cyclodextrin-modified metal organic framework prepared in step (2), a lithium source, a phosphorus source and an iron source, and sintering to obtain the positive electrode material. The invention utilizes the hydroxyl groups on γ-cyclodextrin (γ-CD) to provide coordination sites for metal ions, so that they can coordinate with metal ions to self-assemble to form CD-MOFs. CD-MOFs have a stable pore structure. Evenly distributing them on the surface of lithium iron phosphate positive electrode materials can improve the electron and lithium ion transmission speed of lithium iron phosphate positive electrode materials, thereby improving the discharge capacity and cycle performance of the materials. However, the disadvantage is that the invention uses relatively expensive drugs such as γ-cyclodextrin and 2-methylimidazole.

[0005] Chinese patent application publication number CN 111099569 A discloses a method for preparing a reduced graphene oxide / carbon material coated lithium iron phosphate material, wherein a graphene oxide / polyvinyl pyrrolidone coated lithium iron phosphate precursor is prepared in a graphene oxide and polyvinyl pyrrolidone solution by a hydrothermal method, and a reduced graphene oxide / carbon material coated lithium iron phosphate material is obtained by high-temperature sintering in an inert gas. However, the hydrothermal method has high energy consumption, large amounts of polyvinyl pyrrolidone are used, and high production costs.

[0006] Surface coating, especially surface carbon layer, is an effective way to improve the conductivity and electrochemical performance of materials. However, carbon-based materials generally need to be subjected to high temperature (greater than 750°C) to obtain a high degree of graphitization and excellent conductivity, while iron-based phosphate cathode materials need to be subjected to high temperature (greater than 750°C) to avoid the formation of inactive Maricite-NaFePO 4 Sodium iron pyrophosphate with low specific capacity needs to be prepared under relatively low temperature conditions (less than 750°C), which leads to insufficient carbonization of conventional organic carbon sources and low conductivity.

[0007] Therefore, how to overcome the complex phosphate Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 The defects of poor electronic conductivity, poor discharge capacity and poor rate performance are problems that need to be urgently solved in this field. Summary of the invention

[0008] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a sodium polyanion positive electrode material.

[0009] Another object of the present invention is to provide a sodium polyanion positive electrode material prepared by the above preparation method.

[0010] Another object of the present invention is to provide an application of the above-mentioned sodium polyanion positive electrode material. The object of the present invention is achieved by the following technical solutions: A method for preparing a sodium polyanion positive electrode material comprises the following steps: (1) dispersing graphene oxide in water, adding β-cyclodextrin and reducing agent solution, and heating the reaction to obtain a stable black dispersed liquid; (2) under heating conditions, adding zinc salt to the black dispersed liquid obtained in step (1), dropping a reducing agent solution, and continuing the reaction to obtain a preliminary reduced graphene oxide / zinc oxide composite solution; (3) The preliminary reduced graphene oxide / zinc oxide composite solution obtained in step (2), a sodium source, a phosphorus source, an iron source and a carbon source are mixed, sand-milled, sprayed and sintered to obtain a sodium polyanion positive electrode material.

[0011] Preferably, the mass ratio of the graphene oxide, β-cyclodextrin and zinc salt in step (1) is 1: (1-10): (0.5-3); more preferably 1: (1.5-9): (0.75-2.5).

[0012] Preferably, the reducing agent solution in step (1) is an ammonia solution, and the mass concentration of the ammonia solution is 20-28%, more preferably 25%; the mass ratio of the graphene oxide to the reducing agent solution is 1:(100-300); more preferably 1:(150-300).

[0013] Preferably, in step (1), the ratio of graphene oxide to black dispersion liquid is 0.5-5 mg:1 mL; more preferably 1.5-5 mg / mL.

[0014] Preferably, the temperature of the heating reaction in step (1) is 50-80°C, more preferably 60°C; and the time is 2-5 h, more preferably 2 h.

[0015] Preferably, the heating temperature in step (2) is 50-80° C., and the reaction time is 2-5 h.

[0016] Preferably, the zinc salt in step (2) is at least one of zinc acetate dihydrate, zinc sulfate and zinc nitrate; more preferably zinc acetate dihydrate.

[0017] Preferably, the reducing agent solution in step (2) is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.1-1 mol / L, more preferably 0.5 mol / L; wherein the molar ratio of the reducing agent to the zinc salt is 1:(1-4), more preferably 1:(2-4).

[0018] Preferably, after sintering in step (3), the sodium source, phosphorus source and iron source in the raw materials react to form a sodium iron phosphate pyrophosphate positive electrode material, and the molar ratio of the three elements of sodium, iron and phosphorus in the sodium iron phosphate pyrophosphate positive electrode material is (4+x):(3-y):4, wherein 0≤x≤0.5, 0<y≤0.3, more preferably 0≤x≤0.15, 0<y≤0.15, most preferably, x is 0 and y is 0.09; the carbon source accounts for 5-20wt% of the theoretical output of the sodium iron phosphate pyrophosphate positive electrode material, more preferably 9wt%; the graphene oxide in step (1) accounts for 0.1-0.5wt% of the theoretical output of the sodium iron phosphate pyrophosphate positive electrode material, more preferably 0.16-0.32wt%.

[0019] Preferably, the sodium source in step (3) is at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium citrate, sodium dihydrogen phosphate and disodium hydrogen phosphate; more preferably sodium carbonate.

[0020] Preferably, the iron source in step (3) is at least one of ferric nitrate, ferric phosphate, ferrous oxalate, ferric oxide, ferric hydroxide, ferrous carbonate and ferrous gluconate; more preferably ferric phosphate.

[0021] Preferably, the phosphorus source in step (3) is at least one of ferric phosphate, sodium pyrophosphate, phosphoric acid, sodium pyrophosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate and ammonium phosphate; more preferably, it is ammonium dihydrogen phosphate.

[0022] Preferably, the carbon source in step (3) is at least one of glucose, sucrose, fructose, citric acid, soluble starch, ascorbic acid, oxalic acid, citric acid, sodium citrate, polyethylene glycol, sodium carboxymethyl cellulose, Ketjen black and acetylene black; more preferably at least one of glucose and polyethylene glycol.

[0023] Preferably, the particle size D50 of the slurry obtained by the sand grinding in step (3) is 200-500 nm, and the solid content of the slurry after sand grinding is 30-50%.

[0024] Preferably, the inlet temperature of the spray in step (3) is 190-290°C, and the outlet temperature is 90-130°C.

[0025] Preferably, the sintering in step (3) is carried out under an inert gas atmosphere, and the inert gas is at least one of a rare gas and nitrogen, more preferably at least one of nitrogen, argon, helium and a hydrogen-argon mixture.

[0026] Preferably, the sintering in step (3) is a staged heating calcination treatment, wherein the first stage treatment temperature is 300-400°C, and the time is 2-5 hours; the second stage treatment temperature is 500-600°C, and the time is 8-15 hours; more preferably, calcination is first performed at 300°C for 3 hours, and then calcination is performed at 530°C for 12 hours.

[0027] Preferably, the heating rate of the sintering in step (3) is 2 to 5°C / min.

[0028] A sodium polyanion positive electrode material prepared by the above preparation method.

[0029] Application of the above-mentioned sodium polyanion positive electrode material.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. Currently, the improvement of the electrochemical performance of sodium polyanion materials by overly simple single-layer coatings is limited, but the thicker carbon coating layer coated to improve conductivity limits the processing performance and cycle performance of the material. In order to make up for the deficiency that two-dimensional graphene is difficult to coat evenly; the present invention uses graphene oxide, β-cyclodextrin and nano zinc oxide in combination. While coating the carbon material, β-cyclodextrin plays a bridging role, tightly connecting the nano zinc oxide particles with the graphene carbon material, providing a channel for electron transfer, and promoting the transfer of electrons, thereby effectively improving the conductivity and electrochemical performance of the material. Therefore, the present invention selects a composite coating route of zinc co-doping and carbon coating synergy to prepare lithium iron phosphate composite materials, which ensures the capacity and rate performance of sodium polyanion materials while also having excellent cycle performance.

[0031] 2. Directly using graphene for mixing will inevitably lead to problems such as uneven mixing and easy agglomeration of the finished product in the later stage, which will affect the effect of graphene and the positive electrode material. Graphene oxide has a high oxygen-containing group and good hydrophilicity, which can stabilize the dispersion of graphene oxide flakes in water. β-cyclodextrin is a cyclic oligosaccharide and a second-generation supramolecular host compound. It has an internal microenvironment with electron hydrophobicity in its cavity structure, and hydrophobic molecules are easily trapped in its cavity by replacing water. At the same time, because it contains many hydroxyl groups, the outside of the cavity is hydrophilic, and it can be attached to the surface of the graphene sheet through strong hydrogen bonds, making the graphene more hydrophilic. The introduction of β-cyclodextrin can stabilize graphene oxide in an aqueous medium, so that graphene oxide does not aggregate for a long time. Thereby promoting the self-assembly of the subsequent in-situ grown ZnO nanoparticles on the graphene nanosheets, realizing uniform monodisperse ZnO nanoparticles, and finally realizing the uniform coating of the surface of the positive electrode particles with graphene and ZnO, thereby realizing that the n-type semiconductor ZnO provides a path for electron transmission.

[0032] 3. β-cyclodextrin is used as a connector between graphene oxide and ZnO nanoparticles. The dispersibility between graphene oxide and ZnO nanoparticles and the interaction with other raw materials are improved through supramolecular host-guest interaction. Then, directly through thermal reduction, graphene oxide is reduced to reduced graphene oxide without destroying the structure of the material, solving the problem of graphene agglomeration and enhancing the electrical conductivity and sodium ion transmission rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a comparison chart of the 10C specific capacity of the materials obtained in Examples 1 to 4 and Comparative Examples 1 to 6.

[0034] Figure 2 10C / 0.2C capacity retention rate of the materials obtained in Examples 1 to 4 and Comparative Examples 1 to 6.

[0035] Figure 3 This is a scanning electron microscope image of the positive electrode material product obtained in Example 1. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0037] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0038] Example 1: Preparation of Carbon-Coated Na 4 Fe 2.91 (PO 4 ) 2 P 2 O 7 (1) 1 g of graphene oxide was added to 200 mL of deionized water, ultrasonically treated and dispersed at high speed. 3 g of β-cyclodextrin and 300 mL of 25 wt% ammonia solution were added to the uniform dispersion. The mixture was heated to 60 °C and vigorously stirred for 2 hours to obtain a stable black dispersion liquid A.

[0039] (2) Add 1.5 g of zinc acetate dihydrate to solution A to dissolve and obtain solution B. Add 34 mL of 0.5 mol / L NaOH solution dropwise to solution B while maintaining the temperature at 60°C and stirring continuously for 2 hours to obtain solution C.

[0040] (3) 211.98 g of sodium carbonate as a sodium source, 438.88 g of ferric phosphate as an iron source, 125.38 g of ammonium dihydrogen phosphate, 37.10 g of glucose, and 18.55 g of polyethylene glycol (molecular weight of 6000) were placed in 1500 mL of deionized water, mixed with the liquid C prepared in step (2), and then sand-milled in a sand mill to obtain a precursor slurry with a solid content of about 30%. The particle size D50 of the particles in the precursor slurry was 300-400 nm; (4) The sand-milled slurry was then dried using a spray drying device at an inlet air temperature of 280°C and an outlet air temperature of 100°C. The dried powdered precursor was heated to 300°C at a heating rate of 3°C / min in a nitrogen atmosphere and calcined at 530°C for 12 h to obtain a positive electrode material.

[0041] Example 2 Compared with Example 1, 3 g of β-cyclodextrin was changed to 9 g of β-cyclodextrin, and the remaining steps were the same.

[0042] Example 3 Compared with Example 1, 1 g of graphene oxide was replaced by 2 g of graphene oxide, and the remaining steps were the same.

[0043] Example 4 Compared with Example 1, 1.5 g of zinc acetate dihydrate was replaced by 2.5 g of zinc acetate dihydrate, and the remaining steps were the same.

[0044] Comparative Example 1 Compared with Example 1, liquid A, liquid B, and liquid C are not prepared, that is, steps (1) and (2) are omitted. In step (3), the sodium source, phosphorus source, iron source, and carbon source are directly mixed with water, sand-milled, sprayed, and sintered, wherein the relevant condition parameters are the same.

[0045] Comparative Example 2 Compared with Example 1, the graphene oxide is not modified, that is, steps (1) and (2) are omitted. In step (3), the sodium source, phosphorus source, iron source, carbon source and the graphene oxide aqueous dispersion are directly mixed, sand-milled, sprayed and sintered, wherein the relevant condition parameters are the same.

[0046] Comparative Example 3 Compared with Example 1, cyclodextrin is not added in step (1), and the remaining steps are the same.

[0047] Comparative Example 4 Compared with Example 1, steps (1) and (2) are omitted. In step (3), 3 g of β-cyclodextrin, a sodium source, a phosphorus source, an iron source, and a carbon source are directly mixed with water, sand-milled, sprayed, and sintered, wherein the relevant condition parameters are the same.

[0048] Comparative Example 5 Compared with Example 1, in step (2), 1.500 g of zinc acetate dihydrate is replaced by 0.556 g of nano zinc oxide, and the subsequent heating reaction is not performed. The remaining steps are the same.

[0049] Comparative Example 6 Compared with Example 1, β-cyclodextrin was replaced by α-cyclodextrin, and the remaining steps were the same.

[0050] Performance Testing (1) Battery assembly method: Positive electrode sheet composition: The positive electrode material is prepared from each embodiment and comparative example, and the conductive carbon black and the binder polyvinylidene fluoride are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone is used as a solvent. After being adjusted into a slurry, it is evenly coated on an aluminum foil with a 150um four-sided coater, dried at 60°C for 4h, and vacuum dried at 120°C for 6h to obtain a positive electrode sheet. A metal sodium sheet is used as a negative electrode sheet, a glass fiber separator is used as a separator, and 1.0 mol / L NaClO 4 The electrolyte composed of ethylene carbonate (EC) + diethyl carbonate (DEC) + fluoroethylene carbonate (FEC) (EC:DEC:FEC = 1:1:0.05 volume ratio) and the positive electrode sheet are assembled into a 2032-type button battery.

[0051] (2) Battery test method: each button cell is subjected to constant current charge and discharge test in a charge and discharge instrument, with a charge and discharge voltage of 2.0-4.0V; the initial discharge specific capacity and the first coulombic efficiency are tested at room temperature at a rate of 0.2C (1C = 120mA / g). Rate test: after 5 charge and discharge cycles at rates of 0.2C, 0.5C, 1.0C, 2.0C, 5.0C, and 10.0C, the 10C / 0.2C capacity retention rate = the discharge capacity of the first cycle of 10C / the discharge capacity of the first cycle of 0.2C. The capacity retention rate is tested by cycling 100 cycles at room temperature at a rate of 2C.

[0052] Table 1 In Example 1, β-cyclodextrin + graphene oxide + zinc oxide cooperate with each other to form a uniformly dispersed mixture and are uniformly coated on the final product, which effectively improves the conductivity of the material and the cycle stability. In Examples 2-4, increasing the amount of β-cyclodextrin, graphene oxide, and zinc oxide added separately will affect the dispersion effect or excessive doping and coating, resulting in poor capacity or effect. Comparative Example 1 has not been improved by coating with β-cyclodextrin, graphene oxide, and zinc oxide composites, and the performance is poor. In Comparative Examples 2-4, 1 or 2 of the β-cyclodextrin + graphene oxide + zinc oxide combination are missing, the synergistic effect is lost, the performance improvement is limited, or even the performance is reduced. In Comparative Example 5, nano zinc oxide is directly used, the in-situ generation process is lacking, and the dispersion effect is poor. Comparative Example 6 replaces β-cyclodextrin with α-cyclodextrin. The inner diameter of the α-cyclodextrin molecular cavity is small, about 0.47 to 0.53 nm, and can only bind to smaller guest molecules, with poor dispersion and connection effects, and the effect improvement is not obvious. The inner diameter of the cavity of β-cyclodextrin is 0.7 to 0.8 nm.

[0053] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a sodium polyanion positive electrode material, characterized in that: The following steps are involved: (1) dispersing graphene oxide in water, adding β-cyclodextrin and reducing agent solution, and heating the reaction to obtain a stable black dispersed liquid; (2) under heating conditions, adding zinc salt to the black dispersed liquid obtained in step (1), dropping a reducing agent solution, and continuing the reaction to obtain a preliminary reduced graphene oxide / zinc oxide composite solution; (3) The preliminary reduced graphene oxide / zinc oxide composite solution obtained in step (2), a sodium source, a phosphorus source, an iron source and a carbon source are mixed, sand-milled, sprayed and sintered to obtain a sodium polyanion positive electrode material.

2. The method for preparing a sodium polyanion positive electrode material according to claim 1, characterized in that: The mass ratio of the graphene oxide, β-cyclodextrin and zinc salt in step (1) is 1: (1-10): (0.5-3); The zinc salt in step (2) is at least one of zinc acetate dihydrate, zinc sulfate and zinc nitrate.

3. The method for preparing a sodium polyanion positive electrode material according to claim 2, characterized in that: The mass ratio of the graphene oxide, β-cyclodextrin and zinc salt in step (1) is 1: (1.5-9): (0.75-2.5); The zinc salt in step (2) is zinc acetate dihydrate.

4. The method for preparing a sodium polyanion positive electrode material according to claim 1, characterized in that: After sintering in step (3), the sodium source, phosphorus source and iron source in the raw material react to form a sodium iron phosphate pyrophosphate positive electrode material, wherein the molar ratio of the three elements of sodium, iron and phosphorus in the sodium iron phosphate pyrophosphate positive electrode material is (4+x):(3-y):4, wherein 0≤x≤0.5, 0<y≤0.3; The carbon source accounts for 5-20wt% of the theoretical output of the sodium iron pyrophosphate positive electrode material; The graphene oxide in step (1) accounts for 0.1-0.5 wt % of the theoretical output of the sodium iron pyrophosphate positive electrode material.

5. The method for preparing a sodium polyanion positive electrode material according to claim 1, characterized in that: The reducing agent solution in step (1) is an ammonia solution, and the mass concentration of the ammonia solution is 20-28%; the mass ratio of the graphene oxide to the reducing agent solution is 1:(100-300); The heating reaction temperature in step (1) is 50 to 80°C and the reaction time is 2 to 5 hours; The heating temperature in step (2) is 50-80°C and the reaction time is 2-5 hours; The reducing agent solution in step (2) is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.1-1 mol / L; wherein the molar ratio of the reducing agent to the zinc salt is 1:(1-4).

6. The method for preparing a sodium polyanion positive electrode material according to claim 1, characterized in that: The sodium source in step (3) is at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium citrate, sodium dihydrogen phosphate and disodium hydrogen phosphate; The iron source in step (3) is at least one of ferric nitrate, ferric phosphate, ferrous oxalate, ferric oxide, ferric hydroxide, ferrous carbonate and ferrous gluconate; The phosphorus source in step (3) is at least one of ferric phosphate, sodium pyrophosphate, phosphoric acid, sodium pyrophosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium tripolyphosphate and ammonium phosphate; The carbon source in step (3) is at least one of glucose, sucrose, fructose, citric acid, soluble starch, ascorbic acid, oxalic acid, citric acid, sodium citrate, polyethylene glycol, sodium carboxymethyl cellulose, Ketjen black and acetylene black.

7. The method for preparing a sodium polyanion positive electrode material according to claim 1, characterized in that: The sintering in step (3) is carried out in an inert gas atmosphere, wherein the inert gas is at least one of a rare gas and nitrogen; The sintering in step (3) is a staged heating calcination process, wherein the first stage is treated at a temperature of 300-400°C for 2-5 hours; the second stage is treated at a temperature of 500-600°C for 8-15 hours; The heating rate of the sintering in step (3) is 2 to 5°C / min.

8. The method for preparing a sodium polyanion positive electrode material according to claim 1, characterized in that: In step (1), the ratio of graphene oxide to black dispersion liquid is 0.5-5 mg:1 mL; The inlet temperature of the spray in step (3) is 190-290°C, and the outlet temperature is 90-130°C; The particle size D50 of the slurry obtained by the sand grinding in step (3) is 200-500 nm, and the solid content of the slurry after sand grinding is 30-50%.

9. A sodium polyanion positive electrode material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the sodium polyanion positive electrode material according to claim 9.

Citation Information

Patent Citations

  • High-electric-conductivity lithium iron phosphate material and preparation method thereof

    CN109301195A

  • Preparation method of reduced graphene oxide / carbon material coated lithium iron phosphate material

    CN111099569A

  • Positive electrode material and preparation method and application thereof

    CN117810403A